Drug release from PLGA microparticles can be slowed down by a surrounding hydrogel - L.A. Lefol; P. Bawuah; J.A. Zeitler; J. Verin; F. Danede; J.F. Willart; F. Siepmann; J. Siepmann (Elsevier, 2023)
This study aimed to evaluate and better understand the potential impact that a layer of surrounding hydrogel (mimicking living tissue) can have on the drug release from PLGA microparticles. Ibuprofen-loaded microparticles were prepared with an emulsion solvent extraction/evaporation method. The drug loading was about 48%. The surface of the microparticles appeared initially smooth and non-porous. In contrast, the internal microstructure of the particles exhibited a continuous network of tiny pores. Ibuprofen release from single microparticles was measured into agarose gels and well-agitated phosphate buffer pH 7.4. Optical microscopy, scanning electron microscopy, differential scanning calorimetry, X-ray powder diffraction, and X-ray μCT imaging were used to characterize the microparticles before and after exposure to the release media. Importantly, ibuprofen release was much slower in the presence of a surrounding agarose gel, e.g., the complete release took two weeks vs. a few days in well agitated phosphate buffer. This can probably be attributed to the fact that the hydrogel sterically hinders substantial system swelling and, thus, slows down the related increase in drug mobility. In addition, in this particular case, the convective flow in agitated bulk fluid likely damages the thin PLGA layer at the microparticles' surface, giving the outer aqueous phase more rapid access to the inner continuous pore network: Upon contact with water, the drug dissolves and rapidly diffuses out through a continuous network of water-filled channels. Without direct surface access, most of the drug "has to wait" for the onset of substantial system swelling to be released.